2021
DOI: 10.22146/jcoemph.62285
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender distribution of pterygium cases from the pterygium surgery social service program

Abstract: Pterygium is an eye condition that causes abnormal growth of fibrous tissue on the sclera. Pterygium could cause vision impairment when it reaches the area that blocks the pupil. Though the cause is still inconclusive, pterygium is associated with older age and male gender. The incidence of pterygium in Yogyakarta remains relatively unreported due to little documentation. This study aimed to report findings from the Pterygium Surgery Social Service Program, focusing on the age and sex distribution from several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…19 According to The Tanjong Pagar survey population aged 40 and older have a higher prevalence of pterygium. 20 Supanji et al 21 from Indonesia also found the mean age being 53.84 ± 10.91 (range: 29 -81). The Riau study, also shows similar findings like ours with the number of cases peaked in the fourth decade.…”
Section: Discussionmentioning
confidence: 87%
“…19 According to The Tanjong Pagar survey population aged 40 and older have a higher prevalence of pterygium. 20 Supanji et al 21 from Indonesia also found the mean age being 53.84 ± 10.91 (range: 29 -81). The Riau study, also shows similar findings like ours with the number of cases peaked in the fourth decade.…”
Section: Discussionmentioning
confidence: 87%
“…16 Hal ini sesuai dengan penelitian Wang dkk ditahun 2020 menunjukan kejadian pterygium tanpa kebiasaan merokok yaitu 70%.16,23 Namun berbeda dengan penelitian yang dilakukan oleh Wangmo dkk ditahun 2021 meneliti terkait dengan distribusi kebiasaan merokok dengan yang tidak merokok dengan hasil pada kejadian pterygium dengan merokok 90,6%. 21 Komorbid hipertensi dengan jumlah tertinggi yaitu memiliki komorbid hipertensi berkisar 574 atau 40,2%. Hal ini sesuai dengan penelitian yang dilakukan Waleed dkk ditahun 2021 meneliti terkait dengan distribusi dan karakteristik komorbid dengan pterygium dengan komorbid hipertensi memiliki nilai paling tinggi, prevalensi hipertensi juga meningkat setiap tahunnya.24,27 Komorbid diabetes melitus dengan nilai 13,8% , diabetes melitus dapat mempengaruhi progresi perkembangan pterygium dengan pembentukan formasi advanced glycation end products (AGEs) terakumulasi pada jaringan fibrosa pada nasal dan temporal konjungtiva.12 Hiperlipidemia pada penelitian ini memiliki hasil 212 atau 22,1% pasien pterygium hal ini sama dengan penelitian yang dilakukan Xiao dkk ditahun 2021 terkait dengan diabetes melitus dan didapatkan hasil sekitar 20,5% atau lebih sedikit dibandingkan dengan yang tidak memiliki komorbid diabetes melitus kemudian untuk hiperlipidemia juga didapatkan hasil lebih tinggi yaitu 50%, menunjukan angka komorbid yang lebih tinggi dibandingkan dengan komorbid diabetes melitus pasien dengan pterygium, akan tetapi belum terdapat perbedaan signifikan antara perbedaan pterygium dengan komorbid hiperlipidemia dan yang tidak memiliki komorbid hiperlipidemia.…”
Section: Cunclassified
“…8 Depending on the population studied, other studies have reported a worldwide prevalence ranging from 1 to 25 percent. 9 There is a wide range of pterygium prevalence in India, ranging from 8.4 to 42%. 10 In Pakistan, 7.4% of cases of Pterygium were recorded in a regional study.…”
Section: Introductionmentioning
confidence: 99%